PENGONTROLAN SINAR LAMPU UNTUK HIDROPONIK BERBASIS MIKROKONTROLER - Firmansyah, Boma; Akbar, Ikmal; Istoto, Enggar Hero; Andik Setiawan, I Made (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Modern hydroponic agriculture requires an automated lighting system that can be controlled to ensure optimal plant growth, especially in indoor environments or areas with limited sunlight. This research designs and implements a microcontroller-based lighting control system using ESP32 integrated with Internet of Things (IoT) technology. The system utilizes a light sensor (LDR) to detect the lighting intensity in the plant area, and then the ESP32 microcontroller processes the data to automatically control the LED lights. Additionally, the system features Wi-Fi connectivity, allowing remote monitoring and control through web-based applications or mobile devices. A scheduling feature for light intensity based on plant growth phases is also implemented to enhance energy efficiency and plant productivity. The test results show that the system can maintain the lighting intensity within the optimal range and provide control flexibility for users through the internet network. By utilizing ESP32 as the control center, this system demonstrates the effectiveness of IoT technology in supporting hydroponic agriculture automation.